Феміністичний дискурс у романах «Люборацькі» А. Свидницького та «Еffi Вriest» Т. Фонтане - Чик, Ольга; Chyk, Olga (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто «чоловічі тексти» А. Свидницького й Т. Фонтане – романи «Люборацькі» та «Effi Briest», які можна означити «феміністичними» з огляду на те, що їхні автори свідомо кидають виклик не так патріархальному літературному канону, як патріархальному суспільству. Типологічна схожість жіночих характерів у А. Свидницького та Т. Фонтане зумовлена близькістю їхніх естетичних принципів: у досліджуваних романах виховання бачимо оновлення підходів до зображення жінки.The article deals with novels “The Liuboratski” by A. Svydnytskyi and “Effi Briest” by Th. Fontane, which can be defined “feminist” since their authors consciously challenge not so a patriarchal literary canon as a patriarchal society. Typological similarities in female characters are conditioned by the proximity of their aesthetic principles. In the novels there are updated approaches to the image of women. Ukrainian and German writers have focused on changing the characteristics of the portrait and the inner world of the female characters in the process of formation of character, emphasizing the discriminatory aspects that did not allow women to take their proper place in society. The problem of the social emancipation of women in the patriarchal Russian and German empires of the second half of the XIX century is also common in the novels.
The Feminist Discourse in the Novels “The Liuboratski” by A. Svydnytskyi and “Effi Briest” by Th. Fontane
Keywords: роман виховання; патріархальне суспільство; жіночий образ; компаративна типологія; the Bildungsroman; a patriarchal society; the image of woman; comparative typology